Post-glacial variability of sea ice cover, river run-off and biological production in the western Laptev Sea (Arctic Ocean) – A high-resolution biomarker study. (1st July 2016) - Hörner, T.; Stein, R.; Fahl, K.; Birgel, D.
Abstract: Multi-proxy biomarker measurements were applied on two sediment cores (PS51/154, PS51/159) to reconstruct sea ice cover (IP25 ), biological production (brassicasterol, dinosterol) and river run-off (campesterol, β-sitosterol) in the western Laptev Sea over the last ∼17 ka with unprecedented temporal resolution. The absence of IP25 from 17.2 to 15.5 ka, in combination with minimum concentration of phytoplankton biomarkers, suggests that the western Laptev Sea shelf was mostly covered with permanent sea ice. Very minor river run-off and restricted biological production occurred during this cold interval. From ∼16 ka until 7.5 ka, a long-term decrease of terrigenous (riverine) organic matter and a coeval increase of marine organic matter reflect the gradual establishment of fully marine conditions in the western Laptev Sea, caused by the onset of the post-glacial transgression. Intensified river run-off and reduced sea ice cover characterized the time interval between 15.2 and 12.9 ka, including the Bølling/Allerød warm period (14.7–12.9 ka). Prominent peaks of the DIP25 Index coinciding with maximum abundances of subpolar foraminifers, are interpreted as pulses of Atlantic water inflow on the western Laptev Sea shelf. After the warm period, a sudden return to severe sea ice conditions with strongest ice-coverage between 11.9 and 11 ka coincided with the Younger Dryas (12.9–11.6 ka). At the onset of the Younger Dryas, a distinct alteration of the ecosystem (reflected in a distinct drop in terrigenous and phytoplankton biomarkers) was detected. During the last 7 ka, the sea ice proxies reflect a cooling of the Laptev Sea spring/summer season. This cooling trend was superimposed by a short-term variability in sea ice coverage, probably representing Bond cycles (1500 ± 500 ka) that are related to solar activity changes. Hence, atmospheric circulation changes were apparently able to affect the sea ice conditions on the Laptev Sea shelf under modern sea level conditions. Highlights: The Laptev Sea was mostly covered by near-shore permanent sea ice between 17.2 and 15.5 ka. An environmental alteration happened between 13 and 12 ka, followed by increasing sea ice cover. The major flooding phase at ∼11 ka at the upper continental slope and ∼9.5 ka on the outer shelf. Increasing sea ice proxies indicate a spring/summer cooling starting 7 ka ago. Fluctuations in sea ice since 6 ka, probably related to solar activity changes (Bond Cycle, 1500 ± 500 years).